Magnetic resonance imaging prognostic factors for survival and relapse in dogs with meningoencephalitis of unknown origin - Gonçalves, Rita; De Decker, Steven; Walmsley, Gemma; Maddox, Thomas W. (Frontiers in Veterinary Science, 2024)
Canine meningoencephalitis of unknown origin (MUO) is a debilitating disease associated with high mortality. The prognostic value of magnetic resonance imaging (MRI) findings for predicting survival at 12 months and long-term relapse remains uncertain. This was a retrospective cohort study evaluating the prognostic value of different MRI variables using multivariable logistic regression and Cox proportional hazards analysis. In total, 138 dogs were presumptively diagnosed with MUO. The most common location for lesions identified on MRI were the white matter tracts of the corona radiata and corpus callosum, followed by the frontal, sensorimotor and temporal cortices. Lower T2 lesion load (p = 0.006, OR = 0.942, CI = 0.902 -0.983) was associated with longer survival and higher T1 post-contrast lesion load (p = 0.023, OR =1.162, CI = 1.021-1.322) was associated with relapse. This study has identified prognostic factors that may help identify dogs at higher risk of death and relapse and therefore guide treatment recommendations.